Logging photo albums,
Three photo albums showing scenes of Spokane, and the Coeur d'Alene area, particularly of logging camps. The photographs are completely unidentified except for a couple of items within the photographs. Two photographs in album #2 identify the lumber company as the B. R. Lewis Lumber Company of Coeur d'Alene, but it is not known if all of the photographs are of that company. Other photographs that are identifiable include the Monroe Street Bridge under construction as well as some scenes of downtown Spokane.